DEFINING THE PRODUCT-BASED NON-CONFORMANCE CLASSIFICATION (Journal of Technology and Operations Management, 2013)
This paper focuses on the identification of non-conformances to facilitate improved product validation and aids the pre-production team in product assessment. The manifestation of mistakes which results in non-conformances and their relationship with the characteristics of the product under validation is explained. A new non-conformance classification has been defined based on the manifestation of mistakes and product characteristics. The classification has been evaluated by experts on consumer electronic products from multinational manufacturing companies through closed and open ended questionnaires. The respondents described the classification to be feasible and applicable in pre-production. The proposed classification contributes to the understanding of mistakes and product quality deficiencies which can be minimised by addressing non-conformances during product validation.